Resonant harmonic elimination pulse width modulation‐based high‐frequency resonance suppression of high‐speed railways. Issue 5 (1st May 2015) - Cui, Hengbin; Song, Wensheng; Fang, Hui; Ge, Xinglai; Feng, Xiaoyun
Abstract : High‐frequency resonances occur frequently and severely disrupt the normal operation of high‐speed railways in China. In order to suppress high‐frequency resonances in traction power supply systems, a resonant harmonic elimination pulse width modulation (RHEPWM) technology was proposed. With this method, harmonics around the resonant frequency in the harmonic source were eliminated, and thus the resonance formation condition was broken and resonances were suppressed. A real‐time simulation of RHEPWM application in high‐speed railway system was realised in OP5600 RT‐Lab simulator. The real‐time simulation results show that the proposed RHEPWM strategy can achieve high‐frequency resonance suppression, improve total power factor of traction drive systems, and reduce total harmonic distortion of pantograph currents.